Genetic diversity and immunogenicity of the merozoite surface protein 1 C-terminal 19-kDa fragment of Plasmodium ovale imported from Africa into China - Qinwen Xu (BMC, 2021)
Abstract Background Merozoite surface protein 1 (MSP1) plays an essential role in erythrocyte invasion by malaria parasites. The C-terminal 19-kDa region of MSP1 has long been considered one of the major candidate antigens for a malaria blood-stage vaccine against Plasmodium falciparum. However, there is limited information on the C-terminal 19-kDa region of Plasmodium ovale MSP1 (PoMSP119). This study aims to analyze the genetic diversity and immunogenicity of PoMSP119. Methods A total of 37 clinical Plasmodium ovale isolates including Plasmodium ovale curtisi and Plasmodium ovale wallikeri imported from Africa into China and collected during the period 2012–2016 were used. Genomic DNA was used to amplify P. ovale curtisi (poc) msp1 19 (pocmsp1 19 ) and P. ovale wallikeri (pow) msp1 19 (powmsp1 19 ) genes by polymerase chain reaction. The genetic diversity of pomsp1 19 was analyzed using the GeneDoc version 6 programs. Recombinant PoMSP119 (rPoMSP119)-glutathione S-transferase (GST) proteins were expressed in an Escherichia coli expression system and analyzed by western blot. Immune responses in BALB/c mice immunized with rPoMSP119-GST were determined using enzyme-linked immunosorbent assay. In addition, antigen-specific T cell responses were assessed by lymphocyte proliferation assays. A total of 49 serum samples from healthy individuals and individuals infected with P. ovale were used for the evaluation of natural immune responses by using protein microarrays. Results Sequences of pomsp1 19 were found to be thoroughly conserved in all the clinical isolates. rPoMSP119 proteins were efficiently expressed and purified as ~ 37-kDa proteins. High antibody responses in mice immunized with rPoMSP119-GST were observed. rPoMSP119-GST induced high avidity indexes, with an average of 92.57% and 85.32% for rPocMSP119 and rPowMSP119, respectively. Cross-reactivity between rPocMSP119 and rPowMSP119 was observed. Cellular immune responses to rPocMSP119 (69.51%) and rPowMSP119 (52.17%) induced in rPocMSP119- and rPowMSP119-immunized mice were found in the splenocyte proliferation assays. The sensitivity and specificity of rPoMSP119-GST proteins for the detection of natural immune responses in patients infected with P. ovale were 89.96% and 75%, respectively. Conclusions This study revealed highly conserved gene sequences of pomsp1 19 . In addition, naturally acquired humoral immune responses against rPoMSP1 were observed in P. ovale infections, and high immunogenicity of rPoMSP119 in mice was also identified. These instructive findings should encourage further testing of PoMSP119 for rational vaccine design. Graphical abstract